DIGITAL TECHNOLOGIES OF TRANSPORTATION AND LOGISTICS SYSTEMS VISIBILITY - A. V. Dmitriev (Стратегические решения и риск-менеджмент, 2019)
The article discusses the introduction of digital traceability technologies in transport and logistics systems, examines the legal framework for digital labeling and traceability of goods, substantiates the platform management concept of transport and logistics systems. According to this concept, the focal point of the transport chain is not the logistics operator, but an integrated digital platform management of transport and cargo flows, uniting all participants and providing a high degree of s transparency and traceability through the supply chain, evaluated the efficiency of the transport and logistics systems based on extensive use of modern digital information and communication technologies, with which it is possible to control orders to carry out the planning, organization, monitoring and control throughout the delivery procedure of goods